2022
DOI: 10.3390/molecules27196704
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and Resveratrol Differentially Decrease Expression of the High-Affinity IgE Receptor (FcεRI) by Human and Mouse Mast Cells

Abstract: Mast cells (MC) synthesize and store proinflammatory mediators and are centrally important in atopic diseases such as asthma and atopic dermatitis. Quercetin a and resveratrol are plant derived polyphenolic compounds with anti-inflammatory properties that inhibit MC degranulation and mediator release. However, the underlying mechanism of these inhibitory effects on MC is poorly understood and it is unclear whether this is a general effect on all MC phenotypes. We have characterized and compared the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 62 publications
(75 reference statements)
1
10
0
Order By: Relevance
“…BMMC were cultured on the surface of the CNC/agarose matrix or on agarose alone for 18 h, and the size and granularity of the cell population was analyzed by flow cytometry ( Figures 3A, B ). Cells cultured on the agarose or CNC/agarose composites formed a normally distributed population of large and granular cells as measured by flow cytometry, similar to our previous studies ( Karamchand et al, 2021 ; Alam et al, 2022 ). To determine the effect of the CNC/agarose composites on cell viability, BMMC were washed with PBS and then exposed to propidium iodide, a DNA chelating dye that fluoresces when bound to DNA ( Benassi et al, 2022 ; Jin et al, 2022 ).…”
Section: Resultssupporting
confidence: 87%
“…BMMC were cultured on the surface of the CNC/agarose matrix or on agarose alone for 18 h, and the size and granularity of the cell population was analyzed by flow cytometry ( Figures 3A, B ). Cells cultured on the agarose or CNC/agarose composites formed a normally distributed population of large and granular cells as measured by flow cytometry, similar to our previous studies ( Karamchand et al, 2021 ; Alam et al, 2022 ). To determine the effect of the CNC/agarose composites on cell viability, BMMC were washed with PBS and then exposed to propidium iodide, a DNA chelating dye that fluoresces when bound to DNA ( Benassi et al, 2022 ; Jin et al, 2022 ).…”
Section: Resultssupporting
confidence: 87%
“…This concentration of R is considered moderate and physiologically relevant for in vivo studies as well [ 69 ]. A recent study uncovered differences in the inhibitory effects of R in mouse bone marrow-derived MCs and the human Laboratory of Allergic Diseases (LAD)2 MC line [ 21 ]. Studies are currently ongoing in our lab aiming to compare the effects of R in mouse and human primary MCs.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported inflammation-enabling functions of bioactive sphingolipid sphingosine-1-phosphate (S1P)-activated MCs in early-phase AD in mice, suggesting that controlling MC reactivity may prevent the development of AD [ 16 , 18 ]. It has been reported that R could inhibit MC inflammatory functions by reducing the expression of the high-affinity receptor for immunoglobulin (Ig)E, FcεRI , on human Laboratory of Allergic Diseases (LAD)2 MC line [ 21 ], preventing an increase in MC numbers in allergic enteritis, colitis [ 22 ], passive cutaneous anaphylaxis [ 23 ], and signal transducer and activator of transcription 3 (Stat3) activation [ 24 ]. Intriguingly, R was reported to not only stimulate S1P signaling [ 25 ] but also to inhibit S1P-producing sphingosine kinase 1 (SphK1) activity [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol inhibits mast-cell activation, crucial in allergic responses, by blocking the MK2/3-PI3K/Akt axis, offering potential for various allergy disorders [ 100 ]. In human LAD-2 cells, resveratrol inhibits substance P, compound 48/80, and IgE-mediated degranulation, reducing pro-inflammatory cytokine release [ 101 ]. It also downregulates FcεRI (high-affinity IgE receptor) expression, further dampening allergic responses [ 101 ].…”
Section: Anti-inflammatory and Immunomodulatory Effects Of Resveratro...mentioning
confidence: 99%
“…In human LAD-2 cells, resveratrol inhibits substance P, compound 48/80, and IgE-mediated degranulation, reducing pro-inflammatory cytokine release [ 101 ]. It also downregulates FcεRI (high-affinity IgE receptor) expression, further dampening allergic responses [ 101 ]. In humans, resveratrol may be effective in reducing allergic symptoms, particularly allergic rhinitis [ 102 ].…”
Section: Anti-inflammatory and Immunomodulatory Effects Of Resveratro...mentioning
confidence: 99%